Evaluating the clinical usefulness of platelet function testing: Considerations for the proper application and interpretation of performance measures - Dahlen, Jeffrey R.; Price, Matthew J.; Parise, Helen; Gurbel, Paul A. (Thrombosis and Haemostasis, 2013)
Various diagnostic and prognostic performance measures have been used to describe the clinical usefulness of platelet function testing in the evaluation and management of patients taking P2Y12 inhibitors, which reduce the risk for thrombosis due to their action on the platelet P2Y12 receptor. Platelet function tests are used to confirm the presence of an antiplatelet effect of a P2Y12 inhibitor, and confirmation that the pharmacodynamic effect is associated with a reduction in the rate of thrombosis. Despite this clear association, enthusiasm for the clinical usefulness of platelet function testing has been tempered based on observed sensitivity, specificity, and positive predictive value for the detection of future thrombotic events. However, evaluating the prognostic utility of a test based on diagnostic performance indicators is not appropriate because prognostic tests are not used to diagnose which patients will have events; instead, they are used to assist in risk stratification. Therefore, when evaluating the usefulness of platelet function testing, diagnostic performance measures such as sensitivity, specificity, and predictive values should focus on diagnostic performance in identifying a pharmacodynamic effect, and prognostic performance should be evaluated using prognostic performance measures such as hazard ratios and net reclassification improvement, which are comparable to other well-established risk factors for cardiovascular events.
Keywords: Platelet function testing; antiplatelet agents; test statistics; platelet reactivity